Human Talent and Its Impact on the Quality of Service in the Rural Community-Based Tourism Sector. Analysis and Theoretical Perspectives - CEJAS MARTÍNEZ, Magda Francisca; NAVARRO CEJAS, Mercedes Carolina; ALDAZ HERNÁNDEZ, Silvia Marieta; YÁNEZ, Carlos Alban; MENDOZA VELAZCO, Derling José (Journal of Environmental Management and Tourism, 2022)
Human talent in the tourism sector necessarily incorporates a global vision for quality improvement and sustainable development. Increased competition and the need to improve quality in tourism are closely linked. The objective of this work was to analyse the role of human talent. To analyse its impact on customer care and service quality in the tourism sector. An analysis and theoretical perspectives on the subject were established. Quality management was analysed as a key axis in the development of the tourism sector. Adequate management and the process that identifies the importance of the professional in the area were determined. A qualitative approach methodology was developed. The design was documentary interpretative. Bibliographic information was collected with theoretical and scientific positions. The material and content approached was based on the theories of tourism service quality. The information collected was collected globally on the web. The information was analysed using the triangulation technique. It is concluded that it is necessary to generate suitable mechanisms for tourism service quality. In addition, the work of the professional in the area must be highlighted to obtain significant achievements. These achievements are the satisfaction of the client who demands a tourist service.